Penegakan Hukum Lingkungan Terhadap Kegiatan Penambangan Illegal Galian C Tanah Urug - Trias Hernanda (Jurnal Justiciabelen, 2021)
This scientific article examines the enforcement of environmental law on the mining activities of excavated land c in the Kudus Regency, illegal excavated land c activities in Kudus Regency have a serious impact as evidenced by the emergence of victims in illegal c excavation sites that are not reclaimed. There are indeed not many illegal landfill land in Kudus Regency, but based on supervision in the field, the activity arises because it is based on economic factors, Kudus Regency itself actually has regulated zoning of the areas permitted for mining activities, things mentioned in Perda No. 16/2012 concerning RTRW, the method used in this study is empirical (nondoctrinal) Based on the results of field research on illegal activities of landfill excavation, it can be concluded that enforcement of illegal activities of landfill excavation c has not been carried out optimally. , this can be seen by the presence of illegal miners who still often do mining by playing cat and mouse with Satpol PP officers